Incidental Vocabulary Learning through Beauty Influencer Content on TikTok: Experiences of Indonesian EFL Students - Tahtida Niska Zahriya; Sri Wahyuni (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Although TikTok has increasingly been discussed in EFL learning, limited attention has been given to how non-educational beauty influencer content supports incidental vocabulary learning. This study addresses this gap by exploring Indonesian EFL students’ experiences and perceived benefits of encountering English vocabulary through beauty content on TikTok. Using a qualitative survey design, data were collected from 12 English Language Education students through open-ended questionnaires, followed by semi-structured interviews with three selected participants. The data were analyzed thematically. The findings show that students encountered English vocabulary incidentally while watching makeup tutorials, skincare and beauty product reviews, product recommendations, and Get Ready with Me videos. Vocabulary noticing and understanding were supported by captions, subtitles, repetition, product demonstrations, visual context, and influencer explanations. Students also used strategies such as re-watching videos, checking dictionaries or translation tools, reading comments, and searching online to clarify unfamiliar words. The study reveals that beauty TikTok content can provide meaningful, interest-driven, and low-pressure vocabulary exposure outside the classroom. It contributes to EFL learning by highlighting the pedagogical potential of everyday digital content as a supplementary resource for contextual vocabulary development.